Practical power systems protection - Hewitson, L. G. (Practical professional books from Elsevier., 2005)
Plant operators, electricians, field technicians and engineers will gain a practical understanding of the role and workings of power system protection systems from this work. An understanding of power systems and their optimized management will increase plant efficiency and performance as well as increasing safety levels. This book provides both the underpinning knowledge and basic calculations needed to understand, specify, use and maintain power protection systems, and the practical techniques required on a daily basis. After studying this book you will have an excellent knowledge of the principles of protection. You will also have a better understanding of the possible problems likely to arise in day-to-day work with power protection systems.